Da luta política à política pública: proposição e materialização de políticas de formação para os funcionários da educação básica - Ribeiro, Rosselini Diniz Barbosa (2021)
The theme of this study is the training policies for basic education employees. Its main objective is to analyze the process of proposing and leading the training, recognizing its limits and potential, especially at a higher level. Linked to this analytical movement, it aims to inventory and analyze training policies for education employees; identify the causes for the discontinuity of higher education (Profuncionário); analyze regulations as propositional efforts to build policies; know and analyze the goals and strategies for proposing a national training policy in national and state education plans and, finally, analyze the isolated experiences for the materialization of the Higher Course in Technology in School Processes and the Undergraduate Course on de Technology in School Processes and Undergraduate Course on Technology of Education and Work Processes. It is a bibliographic, documentary, empirical, qualitative, and administrative data analysis research. Therefore, the analytical categories such as unionization, professionalization, proposition, and materialization guided the construction of this thesis, which is structured in four sections, namely: the union organization of education professionals, the construction of training policy, education employees in the PNEs and PEEs, and the materialization of higher education. These categories are theoretically based on studies by Vicentini and Lugli (2009), Dal Rosso, Cruz, and Rêses (2011), Monlevade (2001, 2014a, 2014b, 2019a, 2020), Antunes (2018), Ball (2006, 2012, 2015, 2016), Mainardes (2006, 2018), Afonso (2003), Burton (2014), Saviani (2010, 2016, 2017), Dourado (2010, 2017), Assis (2015), among others. The study makes a historical analysis of the political struggle and the trajectory for the construction of the identity of basic education workers, through the conflicts of the constitution of the National Confederation of Workers in Education (CNTE), focusing on professionalization as the union entity's main cause, an essential condition for the valuation of the category. In this sense, this thesis demonstrates the role of political, institutional, and union actors, in assuming the defense of a political agenda for the category and in the construction of legal and normative instruments for the proposition of a training policy for education workers, policies of training in national and state education plans. To a lesser extent, it demonstrates the discontinuity of the training policy at a higher level for education workers and the materialization of the few offers of higher-level training courses by CNTE initiatives in partnership with its affiliates and Higher Education Institutions (IES). The approval of normative instruments constitutes an important milestone for the category's struggle agenda and is fundamental for the proposition of training policies. However, they seem insufficient for their materialization as a State policy, given the unpredictability of actions, programs, and projects in the Planning Institutional Strategies of MEC (PEI-MEC). Thus, it concludes that the lack of centrality of goals and strategies of the 2014-2024 PNE aimed at training employees as a State policy, in addition to cuts in funding for the offer of the Profuncionário and the institution of another training logic promote discontinuity of training policies at a higher level for education workers, and reduces the materialization of training courses at a higher level to important initiatives by the CNTE and its affiliates in articulation with Federal Universities and Institutes, without the effective support of MEC.